2004
DOI: 10.1063/1.1760513
|View full text |Cite
|
Sign up to set email alerts
|

Percolation-to-droplets transition during spinodal decomposition in polymer blends, morphology analysis

Abstract: Phase separation kinetics of the off-critical mixture of polystyrene and poly(methylphenylsiloxane) is studied by the time-resolved light scattering and optical microscopy. The results from the light scattering experiments are correlated with the images obtained by the optical microscopic observation in order to find characteristic features of the scattering intensity during the percolation-to-droplets morphology transition. At the beginning of the spinodal decomposition process only a bicontinuous network is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 38 publications
(40 reference statements)
1
27
1
Order By: Relevance
“…Experimental studies also show that linear coarsening does not continue indefinitely for all co‐continuous fluid systems. A decrease in the rate of coarsening beyond a critical domain size has been found for a phase separated system and for a number of mechanically mixed systems . This coarsening behavior is illustrated in Figure (solid line; larger dashed lines will be explained later) where the initial linear coarsening is called the primary coarsening regime, and the subsequent slower nonlinear coarsening is called the secondary coarsening regime.…”
Section: Co‐continuous Fluid System Structures and Quiescent Coarsenimentioning
confidence: 77%
See 2 more Smart Citations
“…Experimental studies also show that linear coarsening does not continue indefinitely for all co‐continuous fluid systems. A decrease in the rate of coarsening beyond a critical domain size has been found for a phase separated system and for a number of mechanically mixed systems . This coarsening behavior is illustrated in Figure (solid line; larger dashed lines will be explained later) where the initial linear coarsening is called the primary coarsening regime, and the subsequent slower nonlinear coarsening is called the secondary coarsening regime.…”
Section: Co‐continuous Fluid System Structures and Quiescent Coarsenimentioning
confidence: 77%
“…The evidence to support this hypothesis is actually based on the observations of Demyanchuk and coworkers and of Lopez‐Barron and Macosko at the terminal transition at tTT, trueλ¯TT. Although Demyanchuk found that spherical droplets formed at a lower phase volume fraction of approximately 0.33, at a slightly higher phase volume fraction of approximately 0.35–0.36, stable “elongated” domains (observed in two dimensions) formed.…”
Section: Co‐continuous Fluid System Structures and Quiescent Coarsenimentioning
confidence: 92%
See 1 more Smart Citation
“…Finally, we would like to point out that CHC model with FHG free energy is not suitable to describe the final stages of phase separation without proper account of hydrodynamic flows 52–54. It has recently been demonstrated55–57 in experiments and that in late stages of phase separation when the bicontinuous network breaks into droplets (which must occur either due to the finite size effect or due to the wetting properties of the bounding walls) the system evolves according to the coalescence‐induced coalescence mechanism 52–54. In this mechanism any process of domains coalescence induces hydrodynamic flow, which pushes other domains towards each other and induces further coalescence events.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a bicontinuous network starts to break and the elongated domains appear in the system which later transforms into the spherical droplets minimizing the free interfacial energy, Figure 3c (150 min). Interestingly (ref 5), breaking of the network shows up in the LS measurements ( Figure 2) by the appearance of two peaks (one coming from the dense system of droplets and one from the bicontinuous network). Very quickly both peaks merge into one peak, which quickly shifts into zero wave vectors.…”
Section: Light Scattering Measurements and Opticalmentioning
confidence: 96%